2022
DOI: 10.1111/jvim.16418
|View full text |Cite
|
Sign up to set email alerts
|

Associations among serum insulin, calprotectin, and C‐reactive protein concentrations in Miniature Schnauzers with idiopathic hyperlipidemia before and after feeding an ultra‐low‐fat diet

Abstract: Background: Miniature Schnauzers (MS) commonly have idiopathic hypertriglyceridemia (HTGL), which is associated with insulin resistance (IR) and a subclinical inflammatory phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Primary (idiopathic) HTG in Miniature Schnauzers often remains subclinical for some time, leading to a late-stage diagnosis and the risk of patients presenting with secondary conditions or complications (e.g., pancreatitis, ophthalmic signs, proteinuria, or even seizures) [ 25 , 29 , 30 ], and can be associated with a subclinical inflammatory phenotype and insulin resistance [ 31 ]. Previous studies revealed HTG to be associated with hypercalprotectinemia, a marker of systemic inflammation [ 32 , 33 , 34 ]. However, serum α 1 -proteinase inhibitor concentrations (α 1 PI, a serum antiprotease), calprotectin, and S100A12 concentrations (inflammatory markers) have not been extensively evaluated in dogs with pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Primary (idiopathic) HTG in Miniature Schnauzers often remains subclinical for some time, leading to a late-stage diagnosis and the risk of patients presenting with secondary conditions or complications (e.g., pancreatitis, ophthalmic signs, proteinuria, or even seizures) [ 25 , 29 , 30 ], and can be associated with a subclinical inflammatory phenotype and insulin resistance [ 31 ]. Previous studies revealed HTG to be associated with hypercalprotectinemia, a marker of systemic inflammation [ 32 , 33 , 34 ]. However, serum α 1 -proteinase inhibitor concentrations (α 1 PI, a serum antiprotease), calprotectin, and S100A12 concentrations (inflammatory markers) have not been extensively evaluated in dogs with pancreatitis.…”
Section: Introductionmentioning
confidence: 99%